Educational Administration Factors Effecting to Digital Technology Competency of Teachers in Schools under Nakhon Si Thammarat Provincial Office of Learning - wanrake, usa; Chongcharoen, Koolchalee; Charueksil, Thitikorn Yawichai (An Online Journal of Education, 2025)
The objectives of this research were to study: 1) the educational administration factors of schools under the Provincial Office of Learning Encouragement; 2) the level of digital technology competencies of teachers; 3) the relationship between educational administration factors and digital technology competencies of teachers; and 4) educational administration factors that affect digital technology competencies of teachers in schools. The sample group consisted of 196 teachers. The research instrument was a questionnaire on educational administration factors with reliability coefficients of .97 and digital technology competency of teachers with reliability coefficients of .98, respectively. Data were analyzed using mean, standard deviation, Pearson’s simple correlation coefficient and stepwise multiple regression analysis. The results of the research found that: 1) all aspects of educational administration factors were at a high level; 2) overall digital technology competency of teachers was at a high level; 3) school administration factors have a positive relationship with digital technology competency of teachers at a statistical significance of .01; and 4) educational administration factors that affected digital technology competencies of teachers at the .01 level of statistical significance were that of participatory administration, that of information technology, that of leadership of the school administrator and all factors can predict digital technology competency of teachers at 70.20 percent.